Low-carbon development vector in circular economy - I. S. Belik; N. L. Nikulina (Вестник университета)
Within the framework of the Industry 4.0 concept, transition from a linear economy model to a circular economy model aimed at energy saving, regenerative green production, circulation, and consumption is becoming increasingly relevant. The purpose of the study is to substantiate the low-carbon development model consistency with the goals and objectives of circular economy (hereinafter referred to as CE) for subsequent development of a green growth strategy. Objectives of the study: to use the criteria and methods of CE to develop a toolkit for transition to low-carbon economy and to formulate its development strategy. The study used general scientific methods, in particular, analysis, synthesis, and periodization. In the course of the study the criteria for green economy growth have been identified, and in accordance with them the stages of CE have been established such as conceptual, institutional, and regulatory. The author’s variant of the combined regulatory system based on a combination of administrative and economic measures has been proposed. Matrices of problem situations by individual types of activity have been formed. As the study result, the authors outlined the circular economy stages, substantiated the possibility of low-carbon transformation within the framework of CE, relying on carbon emissions management, low-carbon technologies and a system of financing “green” projects implementation. The tools to stimulate “green” growth have been defined: a tax on greenhouse gas emissions, emissions trading system, subsidizing alternative energy, environmental projects, energy-saving technologies development and their implementation into the production process. The novelty of the study lies in a scheme development for building a low-carbon economic development strategy aimed at achieving the goals of reducing greenhouse gas emissions at the level of both the region and industrial enterprises.